Egyptian dermatologists attitude toward telemedicine amidst the COVID19 pandemic: a cross-sectional study. (17th February 2022) - Elsaie, Mohamed L.; Shehata, Hany A.; Hanafi, Noha S.; Ibrahim, Shady M.; Ibrahim, Hany S.; Abdelmaksoud, Ayman
Abstract: Background: Telemedicine involves distant exchange of medical information between health providers and patients via a telecommunication device with/without the aid of an audiovisual interactive assistance. The current COVID 19 pandemic impact on health services mandated an utmost readiness to implement telemedicine which in part is dependent on health care providers willingness to adopt such platforms. Aim: The aim of this cross sectional study was to assess knowledge and attitude toward telemedicine Egyptian dermatologists amidst the COVID 19 pandemic. Patients and methods: A cross sectional study was designed and data were collected using structured self-administered online questionnaires. Results: Dermatologists had a good knowledge about telemedicine (mean 4.17 ± 1.63; p  < .05). Of those completing the questionnaire, 193 (68.9%) were familiar with the term 'telemedicine' and 164 (58.6%) were familiar with tools like teleconferencing. The majority of responding dermatologists 227 (81.1%) were confident that the COVID 19 pandemic is a good opportunity to start applying telemedicine protocols however the majority 234 (83.6%) preferred using it on trial basis at first before full implementation. Conclusion: In conclusion an overall good attitude toward telemedicine was reported with a mean of 3.39 ( p  < .05). Further large scale studies are required to verify such findings.